2019
DOI: 10.1104/pp.19.00324
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Sodium Flux via the Plasma Membrane Na+/H+ Exchanger SOS1 in the Salt Tolerance of Rice

Abstract: Rice (Oryza sativa) stands among the world's most important crop species. Rice is salt sensitive, and the undue accumulation of sodium ions (Na +) in shoots has the strongest negative correlation with rice productivity under long-term salinity. The plasma membrane Na + /H + exchanger protein Salt Overly Sensitive 1 (SOS1) is the sole Na + efflux transporter that has been genetically characterized to date. Here, the importance of SOS1-facilitated Na + flux in the salt tolerance of rice was analyzed in a reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 101 publications
3
125
0
Order By: Relevance
“…On the other hand, a large proportion of Na + ions accumulated in Arabidopsis shoots were loaded into the xylem by transport systems that appeared to couple the movement of Na + to that of nitrate (Alvarez-Aragon and Rodriguez-Navarro, 2017). The nitrate-dependent loading of Na + into the xylem was additive to that of SOS1, a Na/H exchanger mediating Na + efflux at the xylem parenchyma cells (Shi et al, 2002;El Mahi et al, 2019). Nitrate-dependent Na + transport was partially interrupted in the nrt1.1 mutant but not in nrt1.2, implying that unidentified nitrate transporters under the regulation of the NRT1.1 transceptor were involved in this process (Alvarez-Aragon and Rodriguez-Navarro, 2017).…”
Section: Nitrate-sodium Interactionsmentioning
confidence: 99%
“…On the other hand, a large proportion of Na + ions accumulated in Arabidopsis shoots were loaded into the xylem by transport systems that appeared to couple the movement of Na + to that of nitrate (Alvarez-Aragon and Rodriguez-Navarro, 2017). The nitrate-dependent loading of Na + into the xylem was additive to that of SOS1, a Na/H exchanger mediating Na + efflux at the xylem parenchyma cells (Shi et al, 2002;El Mahi et al, 2019). Nitrate-dependent Na + transport was partially interrupted in the nrt1.1 mutant but not in nrt1.2, implying that unidentified nitrate transporters under the regulation of the NRT1.1 transceptor were involved in this process (Alvarez-Aragon and Rodriguez-Navarro, 2017).…”
Section: Nitrate-sodium Interactionsmentioning
confidence: 99%
“…Overexpression of SOS1 of multiple plant species leads to salt tolerance in plants (Shi et al, 2000;Pardo et al, 2006;Oh et al, 2009;Olías et al, 2009). An OsSOS1 loss of function mutant displayed exceptional salt sensitivity that was correlated with excessive Na + uptake and impaired Na + loading into the xylem (El Mahi et al, 2019). NHXs sequester Na + into vacuoles and are used for osmotic adjustment in salt tolerant plants (Apse et al, 1999;Nieves-Cordones et al, 2016).…”
Section: Molecular Mechanisms For Rice Salt Tolerancementioning
confidence: 99%
“…The expression level of SOS1 was significantly higher than that of SOS2 and SOS3. A recent study of the plasma membrane Na+/H+ exchanger reported that the rice SOS1 gene plays a pivotal role in the adaptive response to salt tolerance [51]. It is thought that Arabidopsis SOS1 could play a leading role in modulating ion pumping and exchange within the cell during salt stress events.…”
Section: Atbzip62 Regulates Sos Pathway Genes Under Salt Stress Condimentioning
confidence: 99%